A study on awareness among parents with beta thalassemia major children in government district hospital, Kalaburagi - S Dhanwadkar, Sharanabasappa; Rayee, Ashwini G; H, Sandeep; Kumari N B, Ashwini (Indian Journal of Child Health, 2024)
Background: Thalassemia is a public health problem worldwide. With the high disease burden of thalassemia, low socioeconomic conditions and poor preventive strategies, our patients are left with no other option except the repeated blood transfusion. So prevention is the only tool to reduce the burden of this disease. This study was done to identify the gap in knowledge, attitude and practices (KAP) about β-thalassemia among the parents of beta thalassemia children. So that it will be helpful to reduce the burden of the disease in the society in the near future. Objectives: To assess the Knowledge (K), attitude (A) and practices (P) among parents with beta thalassemia major children regarding beta thalassemia major disease. Materials and Methods: A semi structured pre-validated questionnaire designed to assess the Knowledge, Attitudes and Practices in relation to beta thalassemia major disease was administered to all the parents fulfilling the inclusion criteria. Collected data was analysed. Results: In this study, None of the participants had knowledge about thalassemia before their first child was born. In this study, 76.9% study subjects knew and understood the genetic nature of Thalassemia. In our study, about 75.4% participants didn’t know about premarital screening and 50.8% didn’t know about prenatal diagnosis. About 18.5% of them are practising chorionic villous sampling test. Only 60.0% of them got other siblings of the thalassemia children screened for thalassemia. Only 43.1% received genetic counselling about thalassemia major. Conclusion: It was seen from our study that parents don’t have adequate knowledge, positive attitude and practice on thalassemia major. Health education and periodic counselling of parents and care takers about prevention of thalassemia needs to be implemented at every thalassemia day care centre.